2007
DOI: 10.4102/curationis.v30i2.1081
|View full text |Cite
|
Sign up to set email alerts
|

The management of infant developmental needs by community nurses - Part 1: Description of the responsibilities of community nurses with regard to the management of infant developmental needs

Abstract: This article is one of two that describes the responsibilities of community nurses, according to their legal scope of practice, with regard to the management of developmental needs of infants in primary health care clinics in South Africa. A subsequent article describes the development of guidelines for the support of community nurses to address the developmental needs of infants 0 - 2 years. While evidence confirms that developmental surveillance should be incorporated into the ongoing health care of the infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…RNs played a vital role across all six countries in helping to refer patients outside of the primary care environment when additional services or specialist consultation were required (Ladden et al, 2013, Leech et al, 2007, Lukewich et al, 2014, Rondinelli et al, 2014, Walker et al, 2015, Walsh et al, 2015). One study in Canada reported that 61% of RNs made independent patient referrals to home care, lactation specialists, social workers, dieticians, and occupational therapists (Todd et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…RNs played a vital role across all six countries in helping to refer patients outside of the primary care environment when additional services or specialist consultation were required (Ladden et al, 2013, Leech et al, 2007, Lukewich et al, 2014, Rondinelli et al, 2014, Walker et al, 2015, Walsh et al, 2015). One study in Canada reported that 61% of RNs made independent patient referrals to home care, lactation specialists, social workers, dieticians, and occupational therapists (Todd et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…One study in Canada reported that 61% of RNs made independent patient referrals to home care, lactation specialists, social workers, dieticians, and occupational therapists (Todd et al, 2007). A second study showed that RNs in South Africa acted as the primary liaison for patient needs and referrals (Leech et al, 2007). RNs in the US were the only group of RNs reported to assess patients through telehealth, such as home blood pressure monitoring (Anderson et al, 2012, Stewart et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations